Adoptive Behaviors of Farmers After Training and Their Subsequent Diffusive Behaviors In Uasin Gishu County, Kenya - Ian Shelburne; David E. Lawver; Steven Fraze; Jonathan Ulmer; Charles Stephenson; Juma Magogo (Journal of International Agricultural and Extension Education, 2017)
This study focused on Kenyan farmers in the Moiben area who participated in three agricultural seminars at Twiga demonstration farm. The problem of interest was the need for increased dissemination of improved agricultural practices to enhance production and processing of crops related to food security and socio-economic well-being. The study investigated associations between adoptive behaviors of participants and their subsequent behavior related to diffusing improved practices to others. Data was collected using a demographic questionnaire and two structured interview schedules. Correlational analysis was conducted on post-training behavior variables, using Kendall’s tau calculations. The study found that farmers across the samples who exhibited higher levels of adoption of workshop-recommended innovations also had a moderate to strong likelihood of showing correspondingly higher levels of diffusion-related behavior. It was concluded that these findings align well with Rogers’ (2003) discussion of change-agent credibility, and also with Bandura’s (2006) work on social modeling and perceived self-efficacy. It was recommended that offering community-based agricultural seminars such as those in this study be continued and expanded, as an important component in a pluralistic model of agricultural extension methodology for Sub-Saharan Africa. It was further recommended that farmers who adopt improved practices learned in training be identified specifically for further interventions related to implementation and diffusion of agricultural innovations.
Keywords: Technology; innovations; adoption; diffusion; Extension; participation; sociallearning framework; social network; farmer-to-farmer